Beberapa Jenis Mangrove Tumbuhan Obat Tradisional di Taman Nasional Sembilang, Banyuasin, Sumatera Selatan (The Potential of Mangrove as Medical Plants in Sembilang Nasional Park Banyuasin South Sumatera) - Sarno Sarno; Hanifa Marisa; Siti Sa’Diah (Jurnal Penelitian Sains, 2013)
The research “Potential Mangrove as Medical Plants in Sembilang National Park Banyuasin South Sumatera” which was conducted in 6 April – 6 October 2013 aims to determine the species of mangrove that can be used as a traditional medicine, to know the parts of mangrove which used as traditional medicine, and utilization the use of mangrove as traditional medicine. The sampling method used was Snowball Sampling, which seek information from the publicor other sources of reliable. Results of the study found that 5 species of mangrove plants are useful as medicinal Acanthus ilicifolius, Acrostichum aureum, Avicennia alba, Sesuvium por-tulacastrum and Xylocharpus granatum. Part of the fruit, sap, leaves and whole plant were used, the utilization was obtained as cure for ulcers, abdominal pain, typhus, itchiness, eye pain that affected by sap of buta-buta plant.